Empowering MSMEs as the Backbone of the National Economy through Credit Insurance - Mayangsari, Jane Berliana; Pratomo, Hananto Budi; Perdana, Mirwan Surya; Mahfudz (LifeSciFi, 2024)
This research explores the effectiveness of credit insurance in empowering MSMEs, which is one of the important sectors in building the national economy. Using a descriptive qualitative method with a case study of Bank Rakyat Indonesia (BRI), this research analyses changes in the Non-Performing Loan (NPL) ratio for MSME loans before and after the implementation of credit insurance. Data was collected from a literature review, reports from the Financial Services Authority (Otoritas Jasa Keuangan/OJK), Bank Indonesia, Ministry of Cooperatives and MSMEs, and BRI's internal reports. The findings show that the implementation of credit insurance lowered the NPL ratio in BRI's MSME segment from 3.5% to 2.1% over two years, supporting the role of credit insurance as a risk mitigation tool that transfers default risk to the insurance company. These results strengthen the theory of risk mitigation and have practical implications for banks in expanding access to secure financing for MSMEs. A limitation of this study is its focus on one bank, which means the results may not be generalizable across the board. Policymakers and regulators are encouraged to consider policies that encourage wider adoption of credit insurance for MSMEs. This study offers insights into developing effective risk mitigation strategies for the MSME credit sector.